Pneumococcal serotype prevalence and antibiotic resistance in children in South and Southeast Asia, 2012-2024 - Tzou-Yien Lin; Cheng-Hsun Chiu; Patrick CY Woo; Abdul Razak Muttalif; Raja Dhar; Leong Choon Kit; Graciela Morales; Egemen Ozbilgili (Taylor & Francis Group, 2024)
This narrative review describes pneumococcal serotype prevalence for invasive disease and carriage and antibiotic resistance among specimens collected from children in countries across South and Southeast Asia from 2012 to 2024. Literature search retrieved 326 articles; 96 were included. The prevalence of pneumococcal serotypes varied geographically and over time after introduction of pneumococcal conjugate vaccine. Serotypes common in both pneumococcal carriage and disease were 6A, 6B, 14, 15B/15C, 19F, and 23F; serotypes 1, 3, 5, 19A, 15A, 10A, and 35B were also common in disease. Most of these serotypes are included in the 13-valent and 10-valent PCV. Carriage and disease isolates remained generally highly susceptible to vancomycin (mostly 100%) and levofloxacin (mostly >97%). These findings indicate that vaccine-preventable serotypes contribute significantly to pneumococcal disease burden in children in South and Southeast Asia. Consistency of national immunization programs with World Health Organization recommendations may reduce rates of pneumococcal disease in this region.